Assessment of Translation Competence Development Needs of Foreign Language Majors at Guangxi University of Foreign Languages - Liang, Minna; Panyanuwat, Anurak; Rupavijetra, Phetcharee; Lomlai, Supalucsana (Science Insights Education Frontiers, 2025)
This study investigated the translation competence (TC) development needs of foreign language majors at Guangxi University of Foreign Languages (GUFL) amid the AI-driven transformation of the translation industry. Employing a quantitative approach, the study administered a questionnaire to a sample of 359 students, with data analyzed via SPSS for descriptive statistics, correlation, and gap analysis. The research identified ten TC dimensions: Strategic Competence (SC), Critical Thinking (CT), Language Competence (LC), Intercultural Competence (IC), Translation Knowledge (TK), Thematic Competence (ThC), Technology Competence (TechC), Personal Competence (PC), Interpersonal Competence (IpC), and Project Management Competence (PMC). Results revealed significant gaps between current and expected levels of TC across all dimensions (p<0.001), with the largest disparities observed in LC and SC. Correlation analysis demonstrated strong interdependencies among all dimensions, and CT emerges as a central connector linking SC, LC, and IC. CT also showed strong correlations with TK, ThC, TechC, and PMC, and moderate correlations with PC and IpC. The findings validated the holistic nature of TC and highlighted the urgency to integrate human-centric communication with digital literacy in translator training. Based on empirical survey results and relevant theories, an Integrated Digital and Human Communication Platform is proposed to address the needs of TC development. The study enriched the literature on TC models and provided valuable insights for translation education.